Dampak Efektivitas Rantai Distribusi Perdagangan bagi Peningkatan Daya Saing Daerah (Studi pada Pengaturan Distribusi Perdagangan Kopi di Kabupaten Jombang) - Alex Srihono (Journal of Regional Economics Indonesia, 2022)
Efforts to strengthen regional competitiveness are strongly influenced by sectoral performance. In the context of competitive competitiveness, the diversity of sectors that determine regional competitiveness must be strengthened through the effectiveness of the trade distribution chain. However, this opinion still leaves debate regarding how much the effectiveness of the trade distribution chain contributes to the strengthening of sustainable regional competitiveness. Based on these conditions, this study aims to strengthen whether the trade distribution chain is really able to strengthen sustainable regional competitiveness. This research takes a case study in Jombang Regency where the regional economy is contributed by the agricultural sector. Therefore, the case of the distribution chain taken from this research is the commodity of the agricultural sector, especially the commodity of coffee. Based on the results of a questionnaire-based survey on coffee commodity traders, this study found that the level of trade effectiveness was able to create transaction cost efficiencies, thereby creating high economic cost cuts. Transaction costs have so far been suspected of having a major effect on wasting economic resources, distorting the welfare level of the perpetrators, as well as making regional sectoral performance in a weak position. These results are expected to be a reference in formulating the strengthening of the distribution chain of trade in various commodities as a determining variable for regional competitiveness.